PENERAPAN METODE DEMONSTRATION DALAM MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN PRAKTEK PASANGAN BATUBATA KELAS X TKBB SMK NEGERI 2 SURAKARTA - Nugroho, Trie Aji; Roemintoyo, Roemintoyo; Agustin, Rima Sri (Pendidikan Teknik Bangunan, 2014)
ABSTRACT AJI TRIE NUGROHO. K1506053. APPLICATION THE METHOD OFDEMONSTRATION TO IMPROVE LEARNING OUTCOMES IN BRICKINSTALLATION PRACTICE IN GRADE X TKBB SMK 2 Surakarta. Paper, Surakarta: School of Teacher Training and Education, Sebelas Maret University of Surakarta, November 2013. The purpose of this study are: (1) To improve learning outcomes and mastery learning grade X TKBB SMK Negeri 2 Surakarta by applying the method of demonstration in teaching of PDKB subjects particularly in bricks practice. This study is classroom action researches, which are conducted in two cycles, the first cycle begins with the identification of existing problems in the classroom, the planning such as preparation steps learning through the application the method of demonstration, action, observation, evaluation, and reflection to act on the second cycle. The subjects were students of grade X TKBB Building Skills Program SMK Negeri 2 Surakarta academic year 2012/2013. Data obtained through the cognitive observation, affective and psychomotor learners, interviews, observation learners, first cycle and second cycle cognitive tests. The data analysis used qualitative descriptive analysis techniques. Based on the results of the study, showed that the application the method of demonstration can improve learning outcomes of students of grade X TKBB SMK Negeri 2 Surakarta academic year 2012/2013 in the learning of Building Construction Basic Works (PDKB). It can be seen from the results of research. In this classroom action research resultsof cognitive learning percentage is 61.8%, and 91.4% in the second action; For affective and psychomotor outcomes in the readiness of learners in subjects receiving the first cycle (67.64%) and second cycle 80.14%), active learners in subjects following the first cycle (63.32%) and second cycle (80.14%); participation of learners in subjects receiving the first cycle (66.17%) and second cycle (78.67%); mastery learning first cycle (69.85%) and second cycle (79.41 %); ability to conduct demonstration first cycle (70.58%) and second cycle (80.88%); activity in the first cycle of interaction and discussion (67.64%) and second cycle(80.14%); communicating observations and experiments first cycle (67.64%) and second cycle (79.41%); clarity in expressing ideas/concept of the first cycle (69.85%) and second cycle (77.20%); ability learners in comparing learning with real life first cycle (69.11%) and second cycle (81.61%); ability to solve problems first cycle (69.58%) and second cycle (80.14%); comparing the results of discussion first cycle (65.44%) and second cycle (80.88%). The conclusion of this research is the application method of demonstration on learning bricks installation practice can improve learning outcomes of students of grade X TKBB Building Skills Program SMK N 2 Surakarta academic year 2012/2013.